THE ROLE OF PARKS ON PHYSICAL ACTIVITY AND PUBLIC HEALTH - Hamza, Ali; Isah, Muhammad S. (FUDMA Journal of Sciences, 2023)
Regular physical activity has been shown to reduce morbidity and mortality by decreasing heart disease, diabetes, high blood pressure, colon cancer, feelings of depression/anxiety, and weight, while building and maintaining healthy bones, muscles, and joints. Due to increasingly sedentary jobs and an increased relianceon motorized transport, leisure-time physical activity may be important in fulfilling recommended physical activity levels. This paper discussed the role of parks to physical activity and public health. Park-based physical activity is a promising means to satisfy current physical activity requirements. However, there is little research concerning what park environmental and policy characteristics might enhance physical activity levels. This paper discussed the relationships between park benefits, park use, and physical activity, and the antecedents of park use. In this classification scheme, the discussion focuses on park environmental characteristics that could be related to physical activity, including park features, condition, access, aesthetics, safety, and policies. The concluded that parks may facilitate social interactions that are critical in maintaining community cohesion, pride, and social capital. It is further recommended that adequate information should be made to ensure that individuals have knowledge on the use and need of parks.
Keywords: Activity, Parks, Physical, Public Health